At home and abroad: an empirical analysis of innovation and diffusion in energy-efficient technologies - Elena Verdolini; Marzio Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper contributes to the induced innovation literature by extending the analysis of supply and demand determinants of innovation in energy-efficient technologies to account for international knowledge flows and spillovers. In the first part of the paper we select a sample of 38 innovating countries and we study how knowledge related to energy-efficient technologies flows across geographical and technological space. We demonstrate that higher geographical and technological distances are associated with a lower probability of knowledge flow. In the second part of the paper, we use our previous estimates to construct stocks of internal and external knowledge for a panel of 17 countries and present an econometric analysis of the supply and demand determinants of innovation accounting for international knowledge spillovers. Our results confirm the role of demand-pull effects, as proxied by energy prices, as well as that of technological opportunity, as proxied by the knowledge stocks. In particular, this paper provides evidence that spillovers between countries have a significant positive impact on further innovation in energy-efficient technologies.
Keywords: O33; Q55; C13; 330; Innovation; Technology Diffusion; Knowledge Spillovers; Energy-Efficient Technologies